"Not just another meta‐analysis": Sources of heterogeneity in psychosocial treatment effect on cancer survival. (1st January 2019) - Mirosevic, Spela; Jo, Booil; Kraemer, Helena C.; Ershadi, Mona; Neri, Eric; Spiegel, David
Abstract: Background: Currently, there are eight meta‐analyses that address the question whether psychosocial intervention can prolong survival with widely disparate conclusions. One reason for inconsistent findings may be the methods by which previous meta‐analyses were conducted. Methods: Databases were searched to identify valid randomized controlled trials that compared psychosocial intervention with usual care. Hazard ratios (HRs) and their confidence intervals were pooled to estimate the strength of the treatment effect on survival time, and z ‐tests were performed to assess possible heterogeneity of effect sizes associated with different patient and treatment characteristics. Results: Twelve trials involving 2439 cancer patients that met screening criteria were included. The overall effect favored the treatment group with a HR of 0.71 (95% Cl 0.58‐0.88; P = 0.002). An effect size favoring treatment group was observed in studies sampling lower vs higher percentage of married patients' (NNT = 4.3 vs NNT = 15.4), when Cognitive‐Behavioral Therapy was applied at early vs late cancer stage (NNT = 2.3 vs NNT = −28.6), and among patients' older vs younger than 50 (NNT = 4.2 vs NNT = −20.5). Conclusions: Psychosocial interventions may have an important effect on survival. Reviewed interventions appear to be more effective in unmarried patients, patients who are older, and those with an early cancer stage who attend CBT. Limitations of previous meta‐analysis are discussed. Abstract : Psychosocial interventions may have an important effect on survival. Reviewed interventions appear to be more effective in unmarried patients, patients who are older, and those with early cancer stage who attend CBT.